2021
DOI: 10.1161/hypertensionaha.120.16598
|View full text |Cite
|
Sign up to set email alerts
|

Urinary- and Plasma-Derived Exosomes Reveal a Distinct MicroRNA Signature Associated With Albuminuria in Hypertension

Abstract: Urinary albumin excretion (UAE) is a marker of cardiovascular risk and renal damage in hypertension. MicroRNAs (miRNAs) packaged into exosomes function as paracrine effectors in cell communication and the kidney is not exempt. This study aimed to state an exosomal miRNA profile/signature associated to hypertension with increased UAE and the impact of profibrotic TGF-β1 (transforming growth factor β1) on exosomes miRNA release. Therefore, exosomes samples from patients with hypertension with/without UAE were is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 55 publications
2
27
1
Order By: Relevance
“…Considerable research has been conducted over recent years into the molecular mechanisms of hypertension-associated renal pathology; however, most previous studies have focused mainly on protein-coding genes or miRNAs [ 30 , 31 , 34 , 35 , 36 ]. For example, our group revealed an exosomal miRNA signature associated with albuminuria in hypertension [ 29 ]. The lncRNA group has reached special relevance in the last years in health and diseases, but few studies have reported on the role of lncRNA in renal pathology [ 12 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable research has been conducted over recent years into the molecular mechanisms of hypertension-associated renal pathology; however, most previous studies have focused mainly on protein-coding genes or miRNAs [ 30 , 31 , 34 , 35 , 36 ]. For example, our group revealed an exosomal miRNA signature associated with albuminuria in hypertension [ 29 ]. The lncRNA group has reached special relevance in the last years in health and diseases, but few studies have reported on the role of lncRNA in renal pathology [ 12 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated the role of exosomal ncRNAs as biomarkers in urological malignancies, chronic kidney disease, cancer or psoriasis [ 26 , 27 , 28 ]. Our group has recently found that urinary- and plasma-derived exosomes reveal a distinct miRNA signature associated with albuminuria in hypertension, reflecting changes taking place in the kidney [ 29 ]. Nevertheless, a study that analyzes the global ncRNA profile associated with early renal damage in hypertension remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A key feature of hypertension is renal damage, and exosomes have been shown to play a role in this phenomenon. A study observed that in hypertensive patients with albuminuria, the profile of 29 plasma exosomal miRNAs was changed compared to controls [ 62 ]. These miRNAs play significant roles in the development of renal damage in hypertension.…”
Section: The Role Of Exosomes In Hypertensionmentioning
confidence: 99%
“…RNA sequencing and proteomic analysis of urinary exosomes has revealed an exosome signature in the end-organ damage seen during hypertensive disease [182]. For instance, miR-26a, miR-146a and miR-596 have been associated with early kidney damage, albuminuria and a poor prognosis [182,183].…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…RNA sequencing and proteomic analysis of urinary exosomes has revealed an exosome signature in the end-organ damage seen during hypertensive disease [182]. For instance, miR-26a, miR-146a and miR-596 have been associated with early kidney damage, albuminuria and a poor prognosis [182,183]. Indeed, over 48 exosomal proteins and 27 exosomal miRNAs have been found to be differentially expressed between hypertensive patients and healthy controls [184,185].…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%